A new injector concept for multimode operation in gasoline direct injection engines. (August 2014) - Mandumpala Devassy, B; Bakshi, S; Ramesh, A
A gasoline direct injection engine typically operates in multiple fuel preparation modes. In general, at higher loads, a homogeneous mixture is favored, whereas a stratified mixture is preferred at part- and low-load conditions. This is usually achieved by altering the injection parameters and injection strategy with respect to load and speed and through appropriate cylinder and piston geometries. In this article, a new injector concept has been proposed to aid attaining multiple modes in a gasoline direct injection engine. This is achieved by shaping the spray structure to suit the required mixture preparation. Detailed simulations are performed to assess the mixing process in a gasoline direct injection engine using the new injector. The charge preparation at the onset of ignition is studied for different injection modes of the same injector. The results indicate a significant improvement in the mixing process for different modes of operation.